Comparison of rhetorical moves in research articles and abstracts in soft and hard disciplines - Khansari, Delaram (2016)
Research article is a prominent communicative genre among members of the academic discourse community. It constitutes several subgenres at the macro level such as abstract and IMRD (Introduction, Method, Results, and Discussion) sections which are organized based on their own communicative purposes. The structure and variations of research articles (RA) and abstracts have been studied extensively across disciplines. It has been postulated that abstract, on its own, include distinctive functions as an independent genre, but at the same time it may follow the content and rhetorical structure of RA. However, the focus of most studies on analyzing RAs has been on the individual section rather than on the entire structure of IMRD sections. The analysis of the rhetorical structure of abstracts in previous studies was also concentrated on the macro-structure rather than on the micro-structure of abstracts. Not many studies have been done on the comparison between abstract and IMRD sections of RA and as a result, the general objective of the study was to explore this aspect in two disciplines (applied Linguistics and Chemistry) as representatives of soft and hard sciences in order to reveal cross disciplinary differences in terms of rhetorical moves and linguistic realizations. Specifically, the present study decided to: a) analyze the rhetorical moves structures of RAs in IMRD sections between two disciplines of AL and CH, b) analyze the rhetorical move structures of abstracts in each IMRD unit across two disciplines, c) compare the rhetorical moves in each IMRD sections between two independent genres of RA and abstract across disciplines, and d) analyze the linguistic realizations in each move in IMRD sections across two disciplines. A mixed-method of qualitative and quantitative analysis was conducted in this cross-disciplinary study. A corpus of 40 (20 from each discipline) research articles were selected for the study. The selected research articles were sourced from 4 ISI journals (2 from each discipline). The corpus was analyzed based on an adapted framework that is based on various contributions of existing models of rhetorical moves in order to give a holistic analysis of the research article and abstract genres. The comparison of related genres (abstract and research article) in this study revealed that not all of the abstracts followed the conventional IMRD structure. In AL discipline, the majority of IMRD RAs included abstract with IMRD structure, however only half of CH abstracts in this study followed their own RAs structures. This result is not congruent with Swales’ (1990) claim who believed that abstracts follow their own RA structures in terms of both content and structure. Analyzing these two genres in terms of the frequency of occurrences of moves in IMRD sections showed a similar trend in the frequency patterns in move selection of each constituents. It can be said that the most frequent move in each IMRD sections of RAs, was also more highlighted in the abstract structures. These results demonstrated the similarity of RA and abstract as two genres in terms of the content and the findings were congruent with Swales’ (1990) who commented that the abstracts reflect the information discussed in the RAs. Additionally, the findings in analyzing the linguistic realizations in both fields revealed that the selection of lexical features in each move depends on the nature of disciplines and the communicative intent of the rhetorical moves. To conclude, this investigation hopes to add new knowledge in the area of writing RA in the field of English for Academic Purposes. Knowing how RAs are written and presented will help writers, especially novice writers, who aim to publish in high impact journals, to write in a manner that will gain acceptance by the discourse communities.